2008
DOI: 10.1128/jvi.01559-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Cytomegalovirus UL84 Virus- and Cell-Encoded Binding Partners by Using Proteomics Analysis

Abstract: Human cytomegalovirus (HCMV) UL84 is a phosphoprotein that shuttles from the nucleus to the cytoplasm and is required for oriLyt-dependent DNA replication and viral growth. UL84 was previously shown to interact with IE2 (IE86) in infected cells, and this interaction down-regulates IE2-mediated transcriptional activation in transient assays. UL84 and IE2 were also shown to cooperatively activate a promoter within HCMV oriLyt. UL84 alone can interact with an RNA stem-loop within oriLyt and is bound to this struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
69
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 46 publications
9
69
0
Order By: Relevance
“…Finally, the viral proteins pUL25, pUL84, and pUL38 were observed. HCMV pUL84 has been previously demonstrated to associate with p53, the NuRD component RBBP4, and importin ␣ (Table 1) (42,63,64). Our results suggest that pUL29/28 interacts with multiple viral and cellular proteins at 24 hpi, including the tumor suppressor protein p53.…”
Section: Hcmv Pul29/28 Interacts With Cellular P53 During Infectionsupporting
confidence: 53%
“…Finally, the viral proteins pUL25, pUL84, and pUL38 were observed. HCMV pUL84 has been previously demonstrated to associate with p53, the NuRD component RBBP4, and importin ␣ (Table 1) (42,63,64). Our results suggest that pUL29/28 interacts with multiple viral and cellular proteins at 24 hpi, including the tumor suppressor protein p53.…”
Section: Hcmv Pul29/28 Interacts With Cellular P53 During Infectionsupporting
confidence: 53%
“…The UL44 protein is structurally homologous to the eukaryotic proliferating cell nuclear antigen (PCNA), which interacts with multiple proteins (31). Recent proteomic analyses demonstrated that the UL44 protein interacts with a variety of proteins, including transcription factors other than viral replication-related proteins (13,(45)(46)(47). Therefore, it is conceivable that pre-RCs including UL44 protein act to optimize the timing of late gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no quantitative or nonquantitative proteomic analysis of the MAM fraction has yet been reported. Although proteomic analyses have identified HCMV virion components (42) and cellular proteins that interact with HCMV products (43,44) as well as defined the HCMV-induced secretome (40), this is the first quantitative proteomic analyses of HCMV-infected HFFs and the effects of virus on ER-mitochondrial contacts. Using this quantitative proteomic approach, we observed dramatic changes in the MAM proteome by late times of HCMV infection, consistent with its global reprogramming of cellular metabolism.…”
mentioning
confidence: 99%